Odpowiedź :
P=a²
36=a²
a=6
a)
a=2r
r=6/2=3
b)
d=2r
d²=a²+a²
d²=2a²
d²=72
d=6√2
r=3√2
36=a²
a=6
a)
a=2r
r=6/2=3
b)
d=2r
d²=a²+a²
d²=2a²
d²=72
d=6√2
r=3√2
P=36 cm kw
a=6cm
a)
r=a/2
r=3cm
b)
r=a/pierwiastek 2
r= 6/pierwistek2 * pierwiastek2/pierwiastek2=6pierwiastek2/2=3 pierwiastek 2
a=6cm
a)
r=a/2
r=3cm
b)
r=a/pierwiastek 2
r= 6/pierwistek2 * pierwiastek2/pierwiastek2=6pierwiastek2/2=3 pierwiastek 2
a)
P=36
36=a²
a=6
r=6:2
r=3
b)
pierwsza przekątna kwadratu=6√2
P=(pierwsza przekątna*druga przekątna):2
36=(6√2*x):2
72=6√2*x
x=72:(6√2)
x=12:√2
x=6√2
r=6√2:2
r=3√2
P=36
36=a²
a=6
r=6:2
r=3
b)
pierwsza przekątna kwadratu=6√2
P=(pierwsza przekątna*druga przekątna):2
36=(6√2*x):2
72=6√2*x
x=72:(6√2)
x=12:√2
x=6√2
r=6√2:2
r=3√2